Analysis of the gap between actual reality and the requirements ofISO14001: 2015 A Case Study at Middle Refineries Company / Al-Dora Refinery - Mohammed Zaidan, Ibrahim; K. AL- Khateeb, Sameer (Journal of Economics and Administrative Sciences, 2020)
The Environmental Management System (EMS) according to ISO 14001:2015 is considered one of the modern and important administrative systems inour time, as it is one of the tools of environmental management after it is an entrypoint for treatment or reducing environmental risks and their effects, especiallythe effects resulting from the oil industry, which is the main source of thetrimester Environmental and waste and depletion of natural resources. Theproblem of the study is manifested in the weakness of the process of diagnosingand reducing the risks of environmental aspects and the resulting environmentalimpacts that have a clear and tangible impact on the lives of workers and thegeneral environment. The aim of the study is to identify the extent of applicationof the environmental management system in (Midland Refineries Company / AlDora Refinery). This is done by determining the size of the gap in the applicationof the environmental specification by using the Checklist and a number ofstatistical analysis methods (arithmetic mean, weights, Percentages), and thediagnosis of environmental aspects. This study reached a set of results, the mostimportant of which was a gap in the application of the above specification at arate of (43%) resulting from a weakness in the application of most of thespecifications of the company, as well as a lack of interest in the implementationof planned programs related to addressing or limiting environmental aspects andtheir impacts. The added value in this study is illustrated by diagnosing thestrengths and weaknesses of each item of the environmental specification withsetting an action plan for eliminating or reducing the gap in the researchedcompany.